Right and Left Ventricular Strain Patterns After the Atrial Switch Operation for D-Transposition of the Great Arteries—A Magnetic Resonance Feature Tracking Study - Burkhardt, Barbara Elisabeth Ursula; Kellenberger, Christian Johannes; Franzoso, Francesca Daniela; Geiger, Julia; Oxenius, Angela; Valsangiacomo Buechel, Emanuela Regina (Frontiers in Cardiovascular Medicine, 2019)
Introduction: Adult survivors of the atrial switch operation for transposition of the great arteries present with a systemic morphologic right ventricle and a subpulmonary morphologic left ventricle. This physiology can be considered a model for the effects of long-term right ventricular pressure overload and of decreased left ventricular afterload. We aimed to determine the impact of these chronically altered loading conditions on myocardial deformation of the ventricles. Materials and methods: Two-dimensional steady state free precession cine images of 29 patients after atrial repair (age 29± 7 years) and 19 controls (24± 10 years; n.s.) were post-processed with feature tracking software (TomTec 2D CPA). Volumes, ejection fractions, global and free wall longitudinal and circumferential strains of both ventricles were compared between both groups. Results: Systemic right ventricular global longitudinal strain was decreased in patients compared to controls (-12.9± 3.3% vs. -18.9± 4.6%, p<0.001), while right ventricular circumferential strain was unchanged (-15.8± 3.4% vs. -15.1± 5%; n.s.). Left ventricular longitudinal strain was similar in both groups (-17± 5.6% vs. -17.5± 4.6%; n.s.), but global left ventricular circumferential strain was lower in patients (-20.7± 4.1% vs. -27.3± 4.5%, p<0.001). The systemic right ventricle, compared to the systemic left ventricle, showed decreased global longitudinal (p<0.001) and circumferential strain (p<0.001). The subpulmonary left ventricle, compared to the subpulmonary right ventricle, demonstrated similar longitudinal (p= 0.223) but higher circumferential strain (p<0.001). Conclusions: In patients after atrial switch repair for transposition of the great arteries, the systemic right ventricle shows poor longitudinal strain, but maintains normal right ventricular circumferential strain. The left ventricle shows higher circumferential strain than the right ventricle, in both systemic and subpulmonary positions.